2010
DOI: 10.1111/j.1399-0012.2009.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent fatigue in liver transplant recipients: a two‐year follow‐up study

Abstract: This longitudinal study shows that fatigue is a chronic problem after LTx and that daily functioning and HRQoL do not improve over time. This study supports the need for intervention programs to address fatigue after LTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 40 publications
3
59
2
2
Order By: Relevance
“…30, nº 1 (enero) dicts negative post-transplant outcomes (Kelly et al, 2006;Zipfel et al, 2002). On the other hand, even in the posttransplant phase, because these patients do not achieve the well-being levels of the general population (Estraviz et al, 2007;Kousoulas et al, 2008) and mental health impairment predicts worse daily functioning -by means of fatigue- (Van Ginneken et al, 2010) and mortality after transplant (Pérez-San-Gregorio, Martín-Rodríguez, Galán-Rodríguez, & Borda-Más, 2009). Likewise, if the psychological complications at the pre-waiting-list-study phase are identified and treated, future disorders will be prevented in next stages such as at the waiting-list and post-transplant phases.…”
Section: Discussionmentioning
confidence: 99%
“…30, nº 1 (enero) dicts negative post-transplant outcomes (Kelly et al, 2006;Zipfel et al, 2002). On the other hand, even in the posttransplant phase, because these patients do not achieve the well-being levels of the general population (Estraviz et al, 2007;Kousoulas et al, 2008) and mental health impairment predicts worse daily functioning -by means of fatigue- (Van Ginneken et al, 2010) and mortality after transplant (Pérez-San-Gregorio, Martín-Rodríguez, Galán-Rodríguez, & Borda-Más, 2009). Likewise, if the psychological complications at the pre-waiting-list-study phase are identified and treated, future disorders will be prevented in next stages such as at the waiting-list and post-transplant phases.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue appears to be a chronic problem after OLT with no change after 2 years, and there is a relation between fatigue and the physical domains of health-related quality of life. 23 It is well-known that these domains of health-related quality of life are reduced after liver transplant. 32 A possible explanation for the presence of fatigue after OLT might be that these patients have multiple comorbidities related to immuno suppressive therapy, such as osteoporosis, arterial hypertension, and chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, the few studies that have examined fatigue in OLT recipients have found that fatigue is still present after liver transplant and remains a major concern. [21][22][23] Reports about psychosocial outcome factors in recipients of liver and kidney transplant procedures are rare and have a limited number of cases. 24 The present crosssectional study aimed to identify clinical factors influencing fatigue and to measure fatigue in patients with a history of OLT and patients with a history of simultaneous/sequential liver and kidney transplant (LKTX) compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a 2-year follow-up study, fatigue remained a persistent problem for liver transplant patients. 23 Different liver disease diagnoses may be associated with different levels of fatigue postoperatively. In one study, physical fatigue continued to be a problem for transplant recipients diagnosed with cirrhosis.…”
Section: Fatiguementioning
confidence: 99%
“…17,18 Sleepiness and fatigue are also common events in patients with chronic liver disease, which can reduce their daily function and their health-related quality of life. [19][20][21][22][23] In addition, impaired neuropsychologic and cognitive functions, such as memory, have been common in liver disease patients and transplant recipients. [24][25][26][27][28] Such deficits may lead to nonadherence to medication and its debilitating consequences, including transplant rejection, infection, and even increased mortality.…”
Section: Introductionmentioning
confidence: 99%